Ticlopidine and Clopidogrel (SR 25990C) Selectively Neutralize ADP Inhibition of PGE1-Activated Platelet Adenylate Cyclase in Rats and Rabbits - Defreyn, G; Gachet, C; Savi, P; Driot, F; Cazenave, J P; Maffrand, J P (Thrombosis and Haemostasis, 1991)
Ticlopidine and its potent analogue, clopidogrel, are powerful inhibitors of ADP-induced platelet aggregation. In order to improve the understanding of this ADP-selectivity, we studied the effect of these compounds on PGE1-stimulated adenylate cyclase and on the inhibition of this enzyme by ADP, epinephrine and thrombin. Neither drug changed the basal cAMP levels nor the kinetics of cAMP accumulation upon PGEj-stimulation in rat or rabbit platelets, which excludes any direct effect on adenylate cyclase or on cyclic nucleotide phosphodiesterase. However, the drop in cAMP levels observed after addition of ADP to PGEr stimulated control platelets was inhibited in platelets from treated animals. In contrast, the drop in cAMP levels produced by epinephrine was not prevented by either drug in rabbit platelets. In rat platelets, thrombin inhibited the PGEX-induced cAMP elevation but this effect seems to be entirely mediated by the released ADP. Under these conditions, it was not surprising to find that clopidogrel also potently inhibited that effect of thrombin on platelet adenylate cyclase. In conclusion, ticlopidine and clopidogrel selectively neutralize the ADP inhibition of PGEr activated platelet adenylate cyclase in rats and rabbits.